2012
DOI: 10.1111/j.1600-079x.2012.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses tumor progression by reducing angiogenesis stimulated by HIF‐1 in a mouse tumor model

Abstract: The sustained expansion of a tumor mass requires new blood vessel formation to provide rapidly proliferating tumor cells with an adequate supply of oxygen and nutrients. Hypoxia-inducible factor-1 (HIF-1) plays an essential role in tumor angiogenesis and growth by regulating the transcription of genes in response to hypoxic stress. This study was designed to investigate the effects of melatonin on tumor growth and angiogenesis, as well as the mechanism underlying the antitumor activities of melatonin. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 46 publications
(60 reference statements)
7
95
2
1
Order By: Relevance
“…To measure the angiogenic level of tumors, we measured the hemoglobin content of each tumor using Drabkin's reagent [24][25][26][27]. As shown in Fig.…”
Section: Ca Inhibits Tumor Angiogenesismentioning
confidence: 99%
“…To measure the angiogenic level of tumors, we measured the hemoglobin content of each tumor using Drabkin's reagent [24][25][26][27]. As shown in Fig.…”
Section: Ca Inhibits Tumor Angiogenesismentioning
confidence: 99%
“…However, many studies have indicated that tumor cells exposed to hypoxia are resistant to TRAIL-induced cancer cell apoptosis [14,26,27] and overcoming inhibition by hypoxia has been a target in solid tumor anticancer therapy using the TRAIL protein [28,29]. Melatonin possesses anti-angiogenic activity by inhibiting stabilization of HIF-1α in the HCT116 cell line [12,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Melatonin may either promote (103) or inhibit (104) angiogenesis depending on the pathological situation. Melatonin inhibits tumor angiogenesis by lowering both basal and hypoxia-induced tumor-cell VEGF production (104)(105)(106). However, melatonin also promotes beneficial angiogenesis in ulcers (103) as well as during wound healing (107) and bone repair (108).…”
Section: Angiogenic Functions Of Circadian Factors or Output Moleculesmentioning
confidence: 99%